Survei Kualitas Air Danau Pandan yang Terletak di Kecamatan Pinangsori Kabupaten Tapanuli Tengah: Ekologi - Dian Fitria M; Rosmasita Rosmasita; Emma Suri Yanti; Ramona Indah Bagariang (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
Lake Pandan had an area of ± 103 hectares located in the village of Parjalihotan Baru, Pinangsori sub-district, Tapanuli Tengah district. The status of Lake Pandan was still rarely known by the people of Central Tapanuli and outside communities of the Central Tapanuli Regency, so research on Lake Pandan was still rarely done. The purpose of this study was to determine the water quality observed from the physical parameters of temperature and depth, while the chemical parameters observed the pH and DO (Dissolved Oxygen) in waters, and to know the hydrological conditions of the lake pandan. The results of the measurement of Lake Pandan water temperature during the study showed that the water temperature at 10 station points ranged from 32.0 ºC - 36.0 ºC, while the depth of the lake ranged from 0.8 m - 1.7 m. DO value or dissolved oxygen content of lake pandan waters range from 4.91 mg / l - 9.03 mg / l. Lake Pandan water pH ranges from 6.8 to 9.02. The hydrological condition of Lake Pandan was formed by the flow of ditches and rivers that flow into Lake Pandan, among others: Aek Kemuning River and Aek Lobu River. While the Lake Pandan outlet naturally flows northward through the Aek Kemuning River and empties into Sitardas Village, Badiri Central Tapanuli.